Diseño y aplicación de una estrategia educativa de promoción y prevención, para la correcta ubicación del cepillo dental en niños de 9 a 12 años del colegio Sintraoficiales en el 2020 (2020)
Toothbrushes are a vital component in disease prevention and, due to lack of knowledge, located near toilets that release viruses, fungi and bacteria when they are discharged. The need for promotion and prevention programs in children is identified since it is there where the first habits are acquired.